1999
DOI: 10.1002/(sici)1096-911x(199911)33:5<486::aid-mpo9>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic deficits in children with Langerhans cell histiocytosis

Abstract: Background Manifestations of Langerhans cell histiocytosis (LCH) in children range from only a rash, to bony lesions accompanied by pain, to major organ disease. When the central nervous system (CNS) is affected, the LCH patient may exhibit signs and symptoms of hypothalamic and pituitary dysfunction (most often resulting in diabetes insipidus or other endocrinopathies) or more global neurologic and neuropsychologic sequelae. Surprisingly, researchers have only recently begun to examine the neuropsychologic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…An earlier report of a patient with LCH involving cerebellar WM also reported significant deficits in global cognitive scores, memory, attention and concentration, and perceptual-organizational capabilities, along with substantial emotional and behavioral problems. 183 These behaviors fall within the domain of the cerebellar cognitive affective syndrome and its neuropsychiatric manifestations, 182,184,185 and they probably reflect involvement of the nonmotor region of cerebellum in the posterior lobe.…”
Section: Neoplasmsmentioning
confidence: 99%
“…An earlier report of a patient with LCH involving cerebellar WM also reported significant deficits in global cognitive scores, memory, attention and concentration, and perceptual-organizational capabilities, along with substantial emotional and behavioral problems. 183 These behaviors fall within the domain of the cerebellar cognitive affective syndrome and its neuropsychiatric manifestations, 182,184,185 and they probably reflect involvement of the nonmotor region of cerebellum in the posterior lobe.…”
Section: Neoplasmsmentioning
confidence: 99%
“…1,2 The disease most commonly involves bone, [3][4][5][6][7][8][9][10] but it is also known to affect a variety of other organ systems. 4,[6][7][8][9][10][11][12][13][14][15][16] Orthopedic surgeons are likely to encounter patients with this disease because bone involvement is seen in 80-100% of cases. [3][4][5][6][7][8]10,14 Although the most common presentation is a solitary lesion of bone, multisystem disease can present in a variety of ways across a wide clinical spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Marked deficits were also identified in attention, visual memory, and managing verbal interference, whilst basic language and other academic abilities were intact in the CNS‐affected group. The only report of longitudinal neuropsychological function in LCH, of an adolescent with significant cerebellar involvement assessed at 12 and 15 years, showed a significant decline in verbal and performance IQ, with full‐scale IQ dropping from 112 to 86 over the 3 year interval 8 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that LCH sufferers with cerebellar changes generally show a progressive clinical and neurological decline, 3,8–10 and LCH has been described as ‘a progressive neuropsychiatric disease’ 9 . The evidence for cognitive decline is, however, lacking, with a single case report constituting the evidence base.…”
Section: Discussionmentioning
confidence: 99%